2021
DOI: 10.3390/nu13061876
|View full text |Cite
|
Sign up to set email alerts
|

Bee Pollen: Current Status and Therapeutic Potential

Abstract: Bee pollen is a combination of plant pollen and honeybee secretions and nectar. The Bible and ancient Egyptian texts are documented proof of its use in public health. It is considered a gold mine of nutrition due to its active components that have significant health and medicinal properties. Bee pollen contains bioactive compounds including proteins, amino acids, lipids, carbohydrates, minerals, vitamins, and polyphenols. The vital components of bee pollen enhance different bodily functions and offer protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 73 publications
0
68
0
Order By: Relevance
“…High nutritional value of bee pollen originates from the content of essential substances such as carbohydrates, proteins, lipids, vitamins, and minerals. Bee pollen also contains important bioactive compounds, such as polyphenols and flavonoids [ 4 , 5 , 6 , 7 , 8 , 9 ] which are known antioxidants [ 10 ] responsible for various biological activities. Furthermore, bee pollen contains all the amino acids essential for human body [ 11 ] in concentrations that are five to seven times higher than those found in traditional high protein foods [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…High nutritional value of bee pollen originates from the content of essential substances such as carbohydrates, proteins, lipids, vitamins, and minerals. Bee pollen also contains important bioactive compounds, such as polyphenols and flavonoids [ 4 , 5 , 6 , 7 , 8 , 9 ] which are known antioxidants [ 10 ] responsible for various biological activities. Furthermore, bee pollen contains all the amino acids essential for human body [ 11 ] in concentrations that are five to seven times higher than those found in traditional high protein foods [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that bee venom acupuncture is effective in musculoskeletal pain, neuropathic pain, neuropsychiatric disorders, immunological diseases, rheumatoid arthritis, Parkinson’s, and skin diseases [ 101 , 102 ]. Similarly, it has been documented that bee pollen and bee bread can regulate ovarian functions, prevent obesity, and ameliorate blood sugar levels [ 103 , 104 ].…”
Section: The Antiviral Effect Of Bee Productsmentioning
confidence: 99%
“…Bee pollen contains bioactive compounds, including proteins, amino acids, lipids, carbohydrates, minerals, vitamins, and polyphenols [ 54 , 68 ]. Considering pollen, it has been reported that the bee pollen’s protein concentration varies between 10% and 40% ( w / w ), depending on the botanical origin.…”
Section: Nutritional Value Bioactive Components and Beneficial Properties Of Bee Productsmentioning
confidence: 99%